Developing Skills for Youthful Leaders Module 1: You Can Be A Leader - Elizabeth B. Bolton; John R. Rutledge; Linda Bowman; Linda Barber (EDIS)
The objects of this lesson are to learn that everyone can be a leader, to understand that leaders differ, and to develop self awareness about your personal leadership style. This document is FCS9088, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. EDIS publication date May 2006.